Desain Strategi Pemasaran Digital Menggunakan Media Sosial Instagram Pada Lely Cake Banjarbaru - Anisa Nur Fitria; Rinova Firman Cahyani (P3M Politeknik Negeri Banjarmasin, 2022)
Lely Cake Banjarbaru is a home industry that has been engaged in food processing bread and cakes since 2019. This business always provides satisfactory service with affordable quality, but is still lacking in marketing strategies, so that customers only include the closest people. The magnitude of the potential of digital marketing is not utilized properly. The purposes of this study are (1) to determine the marketing strategy currently applied to Lely Cake Banjarbaru, and (2) to find out the right marketing strategy through Instagram social media at Lely Cake Banjarbaru. The method used in this research is descriptive. Sources of data used are primary and secondary data. Data collection techniques used are (1) observation, (2) interviews, and (3) documentation. The data analysis technique used the SWOT analysis technique. The results of this study indicate that digital marketing strategies are important at Lely Cake Banjarbaru in managing digital marketing to increase sales. The digital marketing strategy that needs to be implemented and maximized is social media marketing. In order to increase the reach of a wider brand engagement at Lely Cake Banjarbaru through Instagram social media, this can be done by choosing platforms, unique and interesting Instagram account profiles, presenting interesting content, various forms of Instagram content, managing content and schedules, using appropriate hashtags. and relevant, take customers of competitors' products, and increase interaction with customers.